Effectiveness of Adding Different Types of Vitamin C in Improving the Quality of Artemia salina sp. - Ajeng Sukmasari; Nuhman; Ninis Trisyani (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
Artemia is a natural food that contains pigments (canthaxanthin), protein, vitamin C and some essential fatty acids for the growth of fish and shrimp. Artemia contains vitamin C, but it is still suspected that additional vitamin C is needed for larval development, gonad maturity and gamete quality. The purpose of this study was to analyze the effectiveness of vitamin C (ascorbic acid) absorption in the enrichment of Artemia sp. The stocking density of Artemia cysts was 2 g per 2 liters of water with a dose of Vitamin C of 100 mg/liter. The hatching process produced Hatching Percentage (HP) of 54.22% and 53.69%. The method used was laboratory experiment, analyzing Vitamin C absorption using UV-Vis Spectrophotometry method at 450-750 nm wavelength followed by BNT test. UV-Vis spectrophotometer method to determine the level of vitamin C absorbed during the artemia immersion process. Vitamin C absorption concentration after soaking process for 6 hours obtained an average of 0.8640 ppm and 0.8642 ppm. The results of the BNT test showed results with a value of 0.05, so the second type of Vitamin C applied to Artemia was not significantly different.